Immune-Mediated Rippling Muscle Disease Associated With Thymoma and Anti-MURC/Cavin-4 Autoantibodies. Issue 1 (15th January 2023) - Svahn, Juliette; Coudert, Laurent; Streichenberger, Nathalie; Kraut, Alexandra; Gravier-Dumonceau-Mazelier, Alice; Rotard, Ludivine; Calemard-Michel, Laurence; Menassa, Rita; Errazuriz-Cerda, Elisabeth; Chalabreysse, Lara; Osseni, Alexis; Vial, Christophe; et al.
Abstract : Objectives: Rippling muscle disease (RMD) is characterized by muscle stiffness, muscle hypertrophy, and rippling muscle induced by stretching or percussion. Hereditary RMD is due to sequence variants in the CAV3 and PTRF/CAVIN1 genes encoding Caveolin-3 or Cavin-1, respectively; a few series of patients with acquired autoimmune forms of RMD (iRMD) associated with AChR antibody–positive myasthenia gravis and/or thymoma have also been described. Recently, MURC/caveolae-associated protein 4 (Cavin-4) autoantibody was identified in 8 of 10 patients without thymoma, highlighting its potential both as a biomarker and as a triggering agent of this pathology. Here, we report the case of a patient with iRMD-AchR antibody negative associated with thymoma. Methods: We suspected a paraneoplastic origin and investigated the presence of specific autoantibodies targeting muscle antigens through a combination of Western blotting and affinity purification coupled with mass spectrometry–based proteomic approaches. Results: We identified circulating MURC/Cavin-4 autoantibodies and found strong similarities between histologic features of the patient's muscle and those commonly reported in caveolinopathies. Strikingly, MURC/Cavin-4 autoantibody titer strongly decreased after tumor resection and immunotherapy correlating with complete disappearance of the rippling phenotype and full patient remission. Discussion: MURC/Cavin-4 autoantibodies may play a pathogenic role in paraneoplastic iRMD associated with thymoma.